Deep-water sponges (Porifera) from Bonaire and Klein Curaçao, Southern Caribbean - Soest, Rob W.m. Van; Meesters, Erik H.w.g.; Becking, Leontine E. (Zootaxa, 2014)
Four submersible dives off the coast of Bonaire (Caribbean Netherlands) and Klein Curaçao (Curaçao) to depths of 99.5–242 m, covering lower mesophotic and upper dysphotic zones, yielded 52 sponge specimens belonging to 31 species. Among these we identified 13 species as new to science. These are Plakinastrella stinapa n. sp., Pachastrella pacoi n. sp., Characella pachastrelloides n. sp., Geodia curacaoensis n. sp., Caminus carmabi n. sp., Discodermia adhaerens n. sp., Clathria (Microciona) acarnoides n. sp., Antho (Acarnia) pellita n. sp., Parahigginsia strongylifera n. sp., Calyx magnoculata n. sp., Neopetrosia dutchi n. sp., Neopetrosia ovata n. sp. and Neopetrosia eurystomata n. sp. We also report an euretid hexactinellid, which belongs to the rare genus Verrucocoeloidea, recently described (2014) as V. liberatorii Reiswig & Dohrmann. The remaining 18 already known species are all illustrated by photos of the habit, either in situ or ‘on deck’, but only briefly characterized in an annotated table to confirm their occurrence in the Southern Caribbean. The habitat investigated—steep limestone rocks, likely representing Pleistocene fossil reefs—is similar to deep-water fossil reefs at Barbados of which the sponges were sampled and studied by Van Soest and Stentoft (1988). A comparison is made between the two localities, showing a high degree of similarity in sponge composition: 53% of the present Bonaire-Klein Curaçao species were also retrieved at Barbados. At the level of higher taxa (genera, families) Bonaire-Klein Curaçao shared approximately 80% of its lower mesophotic and upper dysphotic sponge fauna with Barbados, despite a distance between them of 1000 km, indicating high faunal homogeneity. We also preliminarily compared the shallow-water (euphotic) sponge fauna of Curaçao with the combined data available for the Barbados, Bonaire and Klein Curaçao mesophotic and upper dysphotic sponges, which resulted in the conclusion that the two faunas show only little overlap.